Effects of Developmental Task Constraints on Kinematic Synergies during Catching in Children with Developmental Delays. Issue 5 (2nd September 2020) - Parvinpour, Shahab; Shafizadeh, Mohsen; Balali, Marzie; Abbasi, Ali; Wheat, Jonathan; Davids, Keith
Abstract: The aim of this study was to examine effects of a task intervention on kinematic synergies in catching. Participants were young children (5.58 ± 0.52 years) with the lowest scores on two-hand catching, according to assessments with the Test of Gross Motor Development-2 (TGMD-2) and were allocated into two groups. The constraints group took part in an 8-week intervention, whereas the control group experienced a typical physical education. Both groups were assessed with motor development and kinematic coordination measures with a catching task with a ball thrown from 2 m distance. Kinematic variables were recorded using a wireless motion capture system. A principal component analysis (PCA) was used to measure the kinematic synergies formed among active body parts. Two synergies that emerged in catching were mainly utilised for "reaching" and "catching" the ball. The control group tended to re-organise the majority of active body parts into two functional units in all phases, whereas the constraints group adapted their active parts into functional units according to the requirement of the novel movement in the transfer task. The findings of this study suggested that task constraints could facilitate object control by re-organisation of active body parts into functional synergies to achieve successful performance.